Material Design Methodology for Optimized Wear-Resistant Thermoplastic–Matrix Composites Based on Polyetheretherketone and Polyphenylene Sulfide; Materials; Vol. 13 iss. 3 - Panin S. V. Sergey Viktorovich; Lyukshin B. A. Boris Aleksandrovich; Bochkareva S. A. Svetlana Alekseevna; Kornienko L. A. Lyudmila Aleksandrovna; Nguyen Dyk An; Le Tkhi Mi Khiep; Panov I. L. Iljya Leonidovich; Grishaeva N. Yu. Nataljya Yurjevna (2020, 2020)
Title screen